2001
DOI: 10.1053/seiz.2001.0602
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of epilepsy and other seizure disorders in an Arab population: a community-based study

Abstract: The PR of epilepsy in Saudi Arabs is within the range of the values reported in most communities. The causes of symptomatic epilepsies revealed a predominance of perinatal and inherited factors. Isolated and non-convulsive seizures were probably under-recognized due to various social and cultural factors as well as to lack of sensitivity of the questionnaire for non-convulsive seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
89
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 26 publications
6
89
1
Order By: Relevance
“…This male excess is presumed to reflect the contribution of etiologic factors such as head trauma, known to be more frequent in males (Annegers et al, 1980; Granieri et al, 1983). Saudi Arabia and Russia reported a 2‐times higher ratio of male to female, similar to our findings (Guekkht et al, 1999; Rajeh et al, 2001). Table 13 shows some results regarding epilepsy prevalence with regard to gender.…”
Section: Discussionsupporting
confidence: 91%
“…This male excess is presumed to reflect the contribution of etiologic factors such as head trauma, known to be more frequent in males (Annegers et al, 1980; Granieri et al, 1983). Saudi Arabia and Russia reported a 2‐times higher ratio of male to female, similar to our findings (Guekkht et al, 1999; Rajeh et al, 2001). Table 13 shows some results regarding epilepsy prevalence with regard to gender.…”
Section: Discussionsupporting
confidence: 91%
“…Among the PWE identified in this population‐based survey, males predominated overall. Similar studies in Saudi Arabia (Al Rajeh et al. 2001) and Kenya (Kaamugisha & Feksi 1988) have also reported male predominance.…”
Section: Discussionsupporting
confidence: 80%
“…A weak association was found in our study (not statistically significant) between gender and epilepsy; this was reported in some other studies (14) as well. Nevertheless, other authors report higher prevalence in male patients (45). We have no explanation for this fact, but for the future, this interesting issue will require larger samples, as total figures for some syndromes (juvenile myoclonic, for example) are too small to draw significant conclusions.…”
Section: Discussionmentioning
confidence: 81%